Water Soaking Disorder in Strawberries: Triggers, Factors, and Mechanisms - Hurtado, Grecia; Knoche, Moritz (Frontiers in Plant Science, 2021)
Water soaking is an important surface disorder of strawberries that limits unprotected field production. The objective was to identify the mechanism(s) of water soaking. Symptomatic fruit show pale, deliquescent patches of skin. This damage extends into the flesh. Numerous cuticular microcracks occurred in water-soaked areas. Water soaking occurred only if the skin was exposed to liquid water. Water soaking was more rapid when the cuticle had been abraded. Water soaking, anthocyanin leakage and water uptake all increased with incubation time. There was a lag phase for water soaking and anthocyanin leakage, but not for water uptake. Susceptibility to water soaking increased with fruit ripening and mass. Incubation in isotonic PEG 6000 increased cuticular microcracking but decreased water soaking and water uptake. Incubation in hypotonic fruit juice (natural and artificial) increased water soaking incidence and severity but reduced water uptake. Incubation in dilute citric and malic acids increased plasma-membrane permeability as indexed by anthocyanin leakage and increased water soaking. Thus, water soaking involves cuticular microcracking, localised water uptake, bursting of cells and the release of organic acids into the apoplast. The damage propagates from cell to cell.